KONSEP KHOLIFATULLAH SEBAGAI MODEL IDEAL KEPEMIMPINAN ORGANISASI SOSIAL - Fathor Rohman (LP2M IAI Miftahul Ulum Pamekasan, 2018)
Example and belief is certainly more devastating impact than on the energy crisis, food, health, transport and water. Because, this is testament to the confidence crisis will be the absence of visionary leaders, competent, and have integrity as well as credible. This is precisely the leadership crisis will exacerbate the nation of Indonesia next and will cause an energy crisis, health, food, even the quality of education any join plummeted, politics and so on will be more severe. In this regard according to Quran conception of man is also often referred to as the Caliph in the sense of power (mandataris, not ruler). In the status that is associated with a variety of human rights, obligations, and responsibilities, all of which constitute the mandate for him. The khalifatullah concept was mentioned explicitly in the Qur'an is a reflection for man how to become leader of the trustful, intelligent, creative, callous, have integrity and are responsible for enforcing all the rules of law and made all the potential and of the natural and human resources as the power to lead. This concept will be examined in this article, how the spirit and values contained in the concept of the khalifatullah it could grow, evolve, and be the spirit of a leadership organization, be it a religious organizations, educational organizations, the political organization, the Organization of regional device (OPD)/dinas, the Organization of the company, as well as State organizations.